1994
DOI: 10.1002/1097-0142(19940901)74:5<1533::aid-cncr2820740507>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the abnormal vitamin k-dependent γ-carboxylation process in human hepatocellular carcinomas

Abstract: Background. An important marker for hepatocellular carcinoma is the presence of des‐γ‐carboxy (abnormal) prothrombin. However, the molecular basis for the reduced carboxylation of prothrombin is unknown. Methods. Two groups of patients were defined according to the absence (Group I, n = 7) or presence (Group II, n = 8) of des‐γ‐carboxy prothrombin. The enzymatic activity of y‐carboxylase and the total microsomal prothrombin concentration were determined in all tumors. The kinetic parameters for the synthetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 18 publications
0
38
0
Order By: Relevance
“…This does not seem to be related to dietary factors and does not yet have prognostic significance. Several studies have suggested that there may be a functional deficit in vitamin K available to hepatoma cells, resulting in a diminished capacity to carboxylate prothrombin on glutamic acid residues, and HCC tissue samples have been found to have a lower concentration of K vitamin in the surrounding tissue Huisse et al, 1994). In addition, the clinical administration of high doses of vitamin K to HCC patients who produce elevated levels of DCP, results in restoration of carboxylation activity, as judged by dramatic decreases of DCP levels to normal (Furukawa et al, 1992;Carr, 1994).…”
mentioning
confidence: 99%
“…This does not seem to be related to dietary factors and does not yet have prognostic significance. Several studies have suggested that there may be a functional deficit in vitamin K available to hepatoma cells, resulting in a diminished capacity to carboxylate prothrombin on glutamic acid residues, and HCC tissue samples have been found to have a lower concentration of K vitamin in the surrounding tissue Huisse et al, 1994). In addition, the clinical administration of high doses of vitamin K to HCC patients who produce elevated levels of DCP, results in restoration of carboxylation activity, as judged by dramatic decreases of DCP levels to normal (Furukawa et al, 1992;Carr, 1994).…”
mentioning
confidence: 99%
“…The best known is alpha-fetoprotein, which we have found to be elevated in about 50% of our HCC patients (Virji et al, 1992). By contrast, the more recently recognized marker DCP (des-γ carboxy prothrombin) has been found to be increased in over 70% of patients with HCC, although it is less specific than AFP, since it is also increased in biliary diseases and by the anticoagulant action of warfarin (Weitz et al, 1993;Huisse et al, 1994;Liebman et al, 1984;Nakao et al, 1991;Liebman et al, 1989;Li et al, 2002,Lefrere et al, 1987,Shah et al, 1987Tsai et al, 1990). The action of warfarin has been identified to be on the vitamin K cycle, in which oxidized vitamin K cannot be cycled back to the reduced and physiologically active form (Fasco et al, 1982), when warfarin was present.…”
Section: Discussionmentioning
confidence: 98%
“…As a result, the underlying normal liver produces mature prothrombin, but HCCs within that liver produce under-carboxylated or immature prothrombin, DCP, one of the more useful HCC serum markers (Weitz et al, 1993;Huisse et al, 1994;Liebman et al, 1984;Nakao et al, 1991;Liebman et al, 1989;Li et al, 2002). The biological significance of this has never been clear, but it has recently been suggested that immature prothrombin or DCP has HCC growth promoting properties (Suzuki et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism causing the elevation of serum PIVKA-II levels in hepatocellular carcinoma patients is proposed to be as follows; (1) vitamin K deficiency in local cancerous tissue due to an abnormal vitamin K uptake of hepatic cancer cells [17][18][19] ; (2) excessive production of a prothrombin precursor (PIVKA) in hepatic cancer cells [18][19][20] ; (3) decline of γ-glutamylcarboxylase activity in hepatic cancer cells 20) ; (4) decline of the ability to use vitamin K due to oxidation-reduction cycle abnormality in hepatic cancer cells; or (5) prothrombin gene abnormality in hepatic cancer cells. 20,21) But details of the mechanism are not known.…”
Section: Discussionmentioning
confidence: 99%